Ergonomics assessments of forestry operations in Omo Forest Reserve, Ogun State, Nigeria (2010)
Research has been intensified In finding ways of improving tree quality, soil conservation, planting and fertilizing techniques and all other factor affecting tree but man who makes success possible for the forest industry, has received far less attention. It is in view of the above that this study assessed the working environment of a logging crew and saw mill workers in Omo Forest Reserve, Ogun State, Nigeria. 42% of the work force reported that the tools and equipments had effects on their working efficiency. A11 the workers were exposed to noise but only 58% asserted that the noise affected their working efficiency and health. Despite their observations, none of the workers interviewed had ever gone for an auditory test and do not use protective equipment such as ear gear because they were not provide with one. An evaluation of the workers' assessment of their living condition revealed that 42% felt that if was good, 33% very good, 17% excellent and 8% stated that it was fair. The study revealed that the level of awareness by the workers was poor and management of the reserve did not take safely measures into consideration. The management should conduct a regular ergonomic assessment of its workforce towards ascertaining their state of health and awareness on precaution measures and safety regulations should be strengthened. It is expedient that the management finds a way of improving the working condition and interacting regularly with the workers in order to improve their working efficiency and productivity.